Codex EU Energy Law. - Deketelaere, Kurt (Lexxion Verlagsgesellschaft mbH, 2012)
HauptbeschreibungThe Codices EU Energy Law and EU Climate Law bring together the most essential, presently applicable legislation, as adopted in the framework of the EU Institutions. Codex EU Energy LawThe liberalisation of the European gas and electricity markets, the awareness to increase the security of energy supply, the necessity to be more energy efficient, and the protection of the environment have triggered the European energy legislation to flourish in recent years. Therefore, an impressive amount of new regulations, directives and decisions on gas, electricity, renewables, biofuels, re.